Quasi-Hadamard Product of Certain ω -Starlike and ω-Convex Functions with respect to Symmetric Points. (26th February 2013) - Tang, Huo; Deng, Guan-Tie
Abstract : The main purpose of this paper is to derive some results associated with the quasi-Hadamard product of certain ω -starlike and ω -convex univalent analytic functions with respect to symmetric points.